ANALISIS IMPLEMENTASI SIKLUS PPEPP DALAM SISTEM PENJAMINAN MUTU INTERNAL PENDIDIKAN ISLAM - Ida Megawati; Febi Febrianto (CV Narasi Khatulistiwa Indonesia, 2026)
This study aims to analyze the implementation of the Determination, Implementation, Evaluation, Control, and Improvement (PPEPP) cycle within the Internal Quality Assurance System at Darul Lughah Wal Karomah Islamic Boarding School. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis, including quality standards, Standard Operating Procedures (SOPs), annual work programs, monitoring and evaluation reports, and other supporting documents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that the PPEPP cycle has been implemented systematically through five interconnected stages. The determination stage was carried out through the formulation of quality standards and supporting quality documents as institutional guidelines. The implementation stage was realized through the execution of work programs and SOPs across organizational units. The evaluation stage was conducted through periodic monitoring and assessment of quality standard achievement, while the control stage was implemented by following up evaluation findings through corrective actions. Furthermore, the improvement stage focused on refining quality standards, revising SOPs, strengthening institutional coordination, and developing work programs as part of a continuous quality improvement process. The study concludes that the implementation of the PPEPP cycle not only strengthens the effectiveness of the Internal Quality Assurance System but also fosters a sustainable quality culture that supports professional, accountable, and continuously improving governance in Islamic educational institutions.